2023
DOI: 10.1002/advs.202304863
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Fast Recyclable and Value‐Added Desulfation Method for Spent Lead Paste via Dual Intensification Processes

Lulu Chai,
Zhiyu Li,
Keyu Wang
et al.

Abstract: The new low‐cost clean pre‐desulfation technology is very important in pyrometallurgy and hydrometallurgy. However, traditional reactors have low space‐time yield and desulfation rate, resulting in high energy consumption and SO2 emissions in the industrial desulfation processes. Herein, dual rotating liquid film reactors (RLFRs) and lime are proposed to construct a recyclable, ultra‐fast, and value‐added desulfation method. Parameter optimization and kinetic calculations prove that the above reactions are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recently, the mechanochemistry method, gaining traction for its high efficiency, eco-friendliness, and energy conservation, has shown tremendous promise in the recovery of valuable metals from waste. Liu et al reported a mechanochemistry method for Cu 0 recovery from printed circuit boards waste; 99.8% of Cu 0 can be transferred to water-soluble CuSO 4 under the optimal conditions, such as the mass ratio of K 2 S 2 O 8 :waste of 3:2, the mechanochemistry rotary speed of 400 rpm, the mass ratio of ball:waste of 60:1, and the mechanochemistry time of 4 h. Chai et al proposed a mechanochemistry method for spent lead paste recovery. They found that the mechanochemistry method greatly shortens the desulfation time of lead paste from 40 min to 10 s with a high desulfation rate of 99.7%; moreover, the sulfation time of lime was reduced from 30 min to 30 s with a sulfation rate of 98.6% with a net profit of 55.99 ¥/ton by cost accounting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the mechanochemistry method, gaining traction for its high efficiency, eco-friendliness, and energy conservation, has shown tremendous promise in the recovery of valuable metals from waste. Liu et al reported a mechanochemistry method for Cu 0 recovery from printed circuit boards waste; 99.8% of Cu 0 can be transferred to water-soluble CuSO 4 under the optimal conditions, such as the mass ratio of K 2 S 2 O 8 :waste of 3:2, the mechanochemistry rotary speed of 400 rpm, the mass ratio of ball:waste of 60:1, and the mechanochemistry time of 4 h. Chai et al proposed a mechanochemistry method for spent lead paste recovery. They found that the mechanochemistry method greatly shortens the desulfation time of lead paste from 40 min to 10 s with a high desulfation rate of 99.7%; moreover, the sulfation time of lime was reduced from 30 min to 30 s with a sulfation rate of 98.6% with a net profit of 55.99 ¥/ton by cost accounting.…”
Section: Introductionmentioning
confidence: 99%